Epitaxial growth of BaSi2 thin films by co-sputtering of Ba and Si for solar cell applications. (3rd June 2021) - Du, Rui; Li, Fei; Yang, Kaiwen; Li, Qiang; Du, Weijie; Zhang, Yiwen; Suemasu, Takashi
Abstract: A new growth method for BaSi2 thin film has been developed by co-sputtering Ba and Si to solve the problem that it is difficult to sputter BaSi2 epitaxial films by a single BaSi2 target. A template layer was first optimized for the subsequent BaSi2 deposition. X-ray diffraction results revealed that BaSi2 epitaxial films with high crystalline quality have been achieved under different growth temperatures between 500 °C–600 °C and different growth rates from 9.37–16.7 nm min −1 . Compared with molecular beam epitaxy, the growth rate of BaSi2 was increased by more than one order of magnitude. The new growth method provides a high-speed, low-cost way for the growth of high-quality BaSi2 thin films. BaSi2 -based devices such as an n-BaSi2 /p-Si heterojunction diode and a Ag/n-BaSi2 Schottky junction diode were also fabricated. We demonstrated the obvious rectifying properties in these junctions, which will be a guide to design and fabricate BaSi2 thin-film solar cells.